National dengue surveillance in the Lao People's Democratic Republic, 2006–2012: epidemiological and laboratory findings - Khampapongpane, Bouaphanh; Lewis, Hannah C; Ketmayoon, Pakapak; Phonekeo, Darouny; Somoulay, Virasack; Khamsing, Ampai; Phengxay, Manilay; Sisouk, Thongchanh; Vongphrachanh, Phengta; Bryant, Juliet E (Western Pacific Surveillance and Response, 2014)
Although dengue has been a public health problem for several decades in the Lao People's Democratic Republic, the magnitude of the disease burden and epidemiological trends remain poorly understood. We analysed national dengue surveillance and laboratory data from 2006 to 2012 by person, place and time. Between 2006 and 2012, the annual dengue notification rate ranged between 62 and 367 cases per 100 000 population with an apparent geographical expansion of transmission throughout the country in recent years and concurrent co-circulation of all four dengue virus subtypes. An electronic database, called Lao People's Democratic Republic Early Warning Alert and Response Network, was introduced in 2008 to provide automated early warning for outbreaks and epidemics. Village outbreaks continue to be notified primarily through event-based surveillance, whereas the weekly indicator-based system provides systematic assessment of annual epidemic cycles. The dengue case data indicate a high and increasing burden of disease. Efforts now need to focus on using available data to prompt more effective outbreak response and to guide the design and implementation of intervention strategies.